2002
DOI: 10.1068/b12840
|View full text |Cite
|
Sign up to set email alerts
|

Reinvention of Tradition as an Urban Image: The Case of Ankara Citadel

Abstract: Debates on urban tourism have been coupled with a widespread discourse on ‘placelessness’, ‘loss of identity’, and ‘standardization’ related to the modernist ideology of planning. In this respect, utilizing this historic urban fabric has become important as a means of recreating an urban image. Ironically, efforts to avoid standardization are caught in another trap of sameness and blandness, because a very similar vocabulary is used in the ability of those tourist-historic places to meet the expectations of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…Especially after 2000, with the influence of neoliberal economic policies such as the loosening of controls on capital flows, deregulation and attraction of foreign investment, the Turkish Government started putting greater emphasis on the wholesale redevelopment of squatter neighborhoods (Karaman, 2013). Part of the policy agenda has been to enhance the image of cities and to brand them in international markets for tourism (Erendil and Ulusoy, 2002;Enlil, 2011). This encouraged planning approval for large-scale housing developments, state-of-the-art office buildings in city centers, shopping malls, culture and convention centers, museums, and luxury hotels and restaurants (Enlil, 2011).…”
Section: Context Of the Study: From Squatter Settlements To Mass Housmentioning
confidence: 99%
“…Especially after 2000, with the influence of neoliberal economic policies such as the loosening of controls on capital flows, deregulation and attraction of foreign investment, the Turkish Government started putting greater emphasis on the wholesale redevelopment of squatter neighborhoods (Karaman, 2013). Part of the policy agenda has been to enhance the image of cities and to brand them in international markets for tourism (Erendil and Ulusoy, 2002;Enlil, 2011). This encouraged planning approval for large-scale housing developments, state-of-the-art office buildings in city centers, shopping malls, culture and convention centers, museums, and luxury hotels and restaurants (Enlil, 2011).…”
Section: Context Of the Study: From Squatter Settlements To Mass Housmentioning
confidence: 99%
“…Owners who could afford to buy properties in these districts moved out over time as Beyoglu lost its appeal as a prestigious housing alternative. Its decline stemmed from long years of public neglect due to both limited financial resources for costly renovation and restoration and to lack of official and private consciousness will for preservation (Erendil & Ulusoy, 2002). Although the majority of CBD functions moved from Beyoglu, so that its upper and middle income residents no longer wished to live there, it was still one of the major tourist centres.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible to give successful examples of the preservation of historical districts from developing countries. For example, the studies of Erendil and Ulusoy (2002) regarding the recovery of Ankara Castle; and Uzun (2003) and Ergun's (2004) comprehensive research which showed that the renovated and restored historical buildings in İstanbul's historical districts produce an effect on those districts' socio-economic development. In a similar study prepared by Özus and Dökmeci (2005), the effects on housing prices of the restoration of the historical buildings in Beyoğlu was examined using a regression analysis which took into account both the characteristics of the buildings and the environment.…”
Section: Introductionmentioning
confidence: 99%